2021
DOI: 10.1111/een.13087
|View full text |Cite
|
Sign up to set email alerts
|

The roles of phenotypic plasticity and adaptation in morphology and performance of an invasive species in a novel environment

Abstract: 1. Species introductions provide insights into how populations respond to new environments and selection pressures through rapid adaptation and adaptive phenotypic plasticity. However, maladaptive responses are increasingly recognised to also be common in nature. The spotted‐wing drosophila, Drosophila suzukii, has rapidly invaded divergent environments providing the opportunity to examine adaptive and maladaptive phenotypic and evolutionary responses to its introduced range. 2. We studied how population densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 102 publications
(133 reference statements)
0
7
0
Order By: Relevance
“…Despite the knowledge that warming‐mediated shifts in body size are likely to have significant consequences for many ecological processes, there are few studies that directly link the changes in body size caused by warming to ecological function in natural settings. The existing studies that fall under this broad research umbrella can typically be grouped into those that: (a) use laboratory experiments to examine the effect of temperature on body size, fecundity, and sometimes flight (Costanzo et al, 2018; Jardeleza et al, 2022; Ohba et al, 2020; Schneider et al, 2020; Soule et al, 2020; Terada et al, 2019; Wonglersak et al, 2021; Xi et al, 2016), versus (b) those that examine correlations between insect body size and ecological functions such as pollination, dispersal, and nutrient cycling (Földesi et al, 2021; Stanbrook et al, 2021; Yang et al, 2016). Here, our goal is to join these two lines of research.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the knowledge that warming‐mediated shifts in body size are likely to have significant consequences for many ecological processes, there are few studies that directly link the changes in body size caused by warming to ecological function in natural settings. The existing studies that fall under this broad research umbrella can typically be grouped into those that: (a) use laboratory experiments to examine the effect of temperature on body size, fecundity, and sometimes flight (Costanzo et al, 2018; Jardeleza et al, 2022; Ohba et al, 2020; Schneider et al, 2020; Soule et al, 2020; Terada et al, 2019; Wonglersak et al, 2021; Xi et al, 2016), versus (b) those that examine correlations between insect body size and ecological functions such as pollination, dispersal, and nutrient cycling (Földesi et al, 2021; Stanbrook et al, 2021; Yang et al, 2016). Here, our goal is to join these two lines of research.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found associations between morphological traits and the environment in invasive insects (e.g. Hernández et al., 2010; Huey, 2000; Jardeleza et al., 2022) or morphology and genotype in invasive and pest insects (Koch et al., 2020; Yadav et al., 2018, 2019). We found few outlier loci associated with the morphological variables measured, and most were associated with wing loading (RDA2: 49 and LFMM:7; Table 3).…”
Section: Discussionmentioning
confidence: 95%
“…As invasive insects spread and persist, they are exposed to novel environments and selection pressures that may vary widely during range expansion into new areas (Gibert et al., 2016; Novak, 2007). Consequently, they may rapidly adapt to their new environmental conditions, for example, via plastic or genetic phenotypic changes (Gibert et al., 2016; Novak, 2007) in life‐history (Common et al., 2020; Wilson et al., 2009), morphological (Huey, 2000; Jardeleza et al., 2022; Koch et al., 2020; Lester, 2005; McGlynn, 1999; Mondor et al., 2007), behavioural (Common et al., 2023; Emiljanowicz et al., 2017; Holway & Suarez, 1999) or physiological (Yu et al., 2012) traits. Such trait adjustments may lead to changes in diet breadth, reproductive investment, dispersal rate and climatic tolerance, which have been linked with insect invasion success (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Ectotherms are particularly vulnerable to environmental variation, as even small temperature changes (1 -2 ℃; Pinsky et al, 2019) can affect physiology and behavior (Lagerspetz & Vainio, 2006;Lang et al, 2023). In response to environmental change, ectotherms can adjust physiological traits (e.g., respiration rate, metabolism, and reproduction; Guderley, 1990;Seebacher et al, 2015) through phenotypic plasticity (Ghalambor et al, 2007;Hartl & Conner, 2004;Jardeleza et al, 2022). This plasticity may enable some marine ectotherms to survive short-term heatwave events, which can help maintain genetic diversity for future selection to act upon (Botero et al, 2015;Gunderson & Stillman, 2015;Huey et al, 2012;Palumbi et al, 2014;Somero, 2010).…”
Section: Introductionmentioning
confidence: 99%